STRATEGI KOMUNIKASI PEMASARAN DALAM REBRANDING MAL PEKANBARU PADA BRAND “HANDPHONE, IT, AND FASHION CENTER” - Silvia Ardianata; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Pekanbaru Mall is the first shopping mall that stands in Pekanbaru City. Pekanbaru Mall opened on 8 November 2003, immediately becoming the largest mall in Pekanbaru at that time. In 2013 Mal Mall did a rebranding on the mall logo, which changes the logo also changed the vision and mission of the Mal Mall in line with its brand, namely "Mobile, IT, and Fashion Center". After rebranding Pekanbaru Mall conducted a marketing communication strategy to introduce the brand and also increase the number of visitors. The purpose of this study was to determine the marketing communication strategy and the factors driving rebranding.This study uses a qualitative method with a descriptive approach, with data collection techniques, namely through interviews, observation, and documentation, with the number of informants totaling 8 people according to the criteria determined through purposive sampling. The data analysis technique in this research is using the Miles and Huberman model and the data validity checking technique is triangulation.  The results showed that, marketing communication strategies in rebranding Mal Pekanbaru on the brand "Mobile, IT, and Fashion Center" refers to the objectives of marketing communication, segmentation and targeting, company differentiation and positioning. Marketing communication strategy in Pekanbaru Mall uses a marketing communication mix, in the form of advertising activities, sales promotions, and events. Factors driving the rebranding in Pekanbaru Mall are, the factors of leader turnover, market saturation, and finally the company's new vision. The obstacles in rebranding the mall logo adjustment with the existing tenants in the mall and also the introduction of new logos with consumers or the public.